Association between acute kidney injury and long-term mortality in patients with aneurysmal subarachnoid hemorrhage: A retrospective study - Xiao, Yangchun; Wan, Jun; Zhang, Yu; Wang, Xing; Zhou, Hanwen; Lai, Han; Chong, Weelic; Hai, Yang; Lunsford, L. Dade; You, Chao; Yu, Shui; Fang, Fang (Frontiers in Neurology, 2022)
Background: Though acute kidney injury (AKI) in the context of aneurysmal subarachnoid hemorrhage (aSAH) worsens short-term outcomes, its impact on long-term survival is unknown. Aim: We aimed to evaluate the association between long-term mortality and AKI during hospitalization for aSAH. Methods: This was a retrospective study of patients who survived >12 months after aSAH. All patients were evaluated at West China Hospital, Sichuan University, between December 2013 and June 2019. The minimum follow-up time was over one year. the maximum follow-up time was about 7.3 years. AKI was defined by the KDIGO (The Kidney Disease Improving Global Outcomes) guidelines, which stratifies patients into 3 stages of severity. The primary outcome was long-term mortality, which was analyzed with Kaplan-Meier curves and Cox proportional hazards models. Results: During this study period, 238 (9.2%) patients had AKI among 2592 patients with aSAH. We confirmed that AKI during care for aSAH significantly increased long-term mortality (median 4.3 years of follow-up) and that risk increased with the severity of the kidney failure, with an adjusted hazard ratio (HR) of 2.08 (95% CI 1.49-2.89) for stage 1 AKI, 2.15 (95% CI 1.05-4.43) for stage 2 AKI, and 2.66 (95% CI 1.08-6.53) for stage 3 AKI compared with patients without AKI. Among patients with an AKI episode, those with renal recovery still had increased long-term mortality (HR 1.96; 95% CI 1.40- 2.74) compared with patients without AKI but had better long-term outcomes than those without renal recovery (HR 0.51, 95% CI 0.27-0.97). Conclusions: Among 12-month survivors of aSAH, AKI during their initial hospitalization for aSAH was associated with increased long-term mortality, even for patients who had normal renal function at the time of hospital discharge. Longer, multidisciplinary post-discharge follow-up may be warranted for these patients. KEYWORDS：Intracranial aneurysm, Subarachnoid hemorrhage, mortality, Acute kidney injury, Prognostic factors, Complication.